Bones. The complete eighth season [videorecording (DVD)] - Hanson, Hart (2013)
Although the team solves some of their most challenging cases yet, madman Christopher Pelant continues his murderous rampage, inching closer to Bones and Booth daily. From solving the mystery of a roller derby darling's demise to uncovering a previously unrecognized 9/11 hero to stopping a pandemic, Bones and the team make one remarkable discovery after another.